KONSEP PENILAIAN BAGI PARA PAMONG BELAJAR DALAM RANGKA PENGENDALIAN MUTU DAN DAMPAK PROGRAM PNF - AkbarMa’ruf (JIV-Jurnal Ilmiah Visi, 2007)
Learning mentor has an important role in implementing NFE programs, especially as a technical functional operator, learning model developer, instructor and evaluator. They should be able to do the evaluation in order to control the quality and the implementation impact of NFE programs. NFE provides educational services which have to be improved continuously in the aspects of planning, implementation, learning achievment and the outcome.